Patterns of shelf margin clinoform: control of the development of deep-water sedimentary systems - Li, Tong; Yan, Detian; Liu, Entao; Zhang, Junfeng; Wei, Xiaosong; Lu, Zeyu; Lin, Xudong (Frontiers in Marine Science, 2025)
The clinothem is the fundamental element of basin infill and plays an important role in the source-to-sink system of deep-water basins. In this study, which is based on 2D and 3D seismic data, the spatiotemporal evolution of clinothems and depositional systems from the Miocene to the Pleistocene in the Qiongdongnan Basin, northern South China Sea, is investigated. The following conclusions are drawn: (1) three variations of clinothems in the Qiongdongnan Basin were recognized respective O-, S- and F-type clinothems; (2) fluctuations in the relative base level, in combination with variations in sediment supply, result in different clinothem patterns that may be used to understand changes in these depositional factors; and (3) the development of O-type clinothem is usually accompanied by slope instability and slumping, leading to mass transport deposits on the basin plain. When suitable transport pathways exist (e.g., shelf canyons) on the shelf-edge or when the F-type clinothem develops, sediments can be dispersed basinward, promoting submarine fan development. Results from this study will help in understanding the sedimentological development of slope and basin plain areas and offers significant insights into the understanding of deep-sea depositional systems.